Estetika Tari Piriang di Ateh Kaco Karya Syofyani Pada Sanggar Syofyani Kota Padang - Suci Adela Rosyadi; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2022)
This study aims to reveal and describe the aesthetic value of the Piriang Dance at Ateh Kaco by Syofyani at the Syofyani Studio, Padang City. This type of research is qualitative research using a descriptive method. The main instrument in this study is the researcher himself and is assisted by supporting instruments such as writing instruments, photo cameras and audio conversion tools. This type of data uses primary data and secondary data. Data collection techniques were carried out employing library research, observation, interviews and documentation. The steps to analyze the data are data reduction, data display, and conclusion verification. The results showed that the form in terms of shape and arrangement of the main elements (motion) consisted of the name of the motion and the description of the motion. From the shape of the supporting elements, the shape and arrangement are that the floor pattern is formed by the formation of dancers. Broadly speaking, there are two-floor patterns, namely straight line patterns such as trapezoid, vertical, and horizontal, and curved lines such as making a circle. This dance is usually danced by nine dancers, namely four male dancers and four female dancers, plus one dancer to steps on the kaco. Weight in dance consists of atmosphere, ideas or ideas, and like. Three elements play a role in performing arts, namely talent, skills, and means of media.